Supervisor's behavioral complexity: Ineffective in the call center - Federico R. León; Andrés Burga-León; Oswaldo Morales (International Journal of Business Science & Applied Management (IJBSAM), 2017)
An ample repertoire of leadership behaviors available to the manager is expected to guarantee his/her effectiveness transcending situations, but research in the call-center context has identified a specific form of effective supervision: people-oriented leadership. The purpose of this paper is to compare the effectiveness of leader behavioral complexity vis-a-vis people-oriented supervision. 268 employees out of 728 of a Peruvian call center filled in an on-line survey that included, among other questionnaires, the Competing Values Framework Managerial Behavior Instrument in reference to their front-line supervisor. The study analyzed the relationships between supervisory leadership and subordinate turnover intention and absenteeism. Behavioral complexity, like people-oriented leadership, predicted subordinate turnover intention but did not predict subordinate absenteeism, which people-oriented leadership did when other leadership orientations (to change, results, processes) were held constant. Our explanations consider that absenteeism is a concrete behavior and turnover intention an abstract attitude. The findings are consistent with the call-center literature, suggest important boundaries to the concept of manager behavioral complexity, and highlight the need for contingency theories of leadership effectiveness.
Keywords: 650; leader behavioral complexity; people-oriented leadership; absenteeism; competing values framework